-: Indonesia - Aprianti, Juwita Dwi (ELATICS JOURNAL, 2025)
This paper explores how narrative suspense is constructed in the works of Shirley Jackson and Jordan Peele. A central technique employed by both artists is the use of layered storytelling that builds tension through the interplay of two interconnected narrative strands. An analysis of Jackson’s fiction and Peele’s films demonstrates that the suspense in their works does not rely on traditional Gothic tropes, but rather on carefully designed plots that deliberately guide and manipulate audience attention. The article begins by outlining the concept of narrative suspense, followed by an examination of the structural techniques employed by Jackson and Peele, and concludes with an analysis of specific narrative strategies in their respective works. By adopting a comparative approach, this study offers insights into the mechanics of suspense storytelling across different media.